2010
DOI: 10.1111/j.1399-0004.2010.01484.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive decision‐making: a qualitative study among couples at increased risk of having a child with retinoblastoma

Abstract: Little is known about the reproductive decision-making process of couples with an increased risk of having a child with retinoblastoma (Rb). A qualitative study was conducted to explore the impact of prospective risk on reproductive decisions, factors influencing these decisions, and the needs of couples with regard to reproductive counselling. Fourteen couples of childbearing age who received genetic counselling between 2002 and 2006 participated in semi-structured interviews in 2008. The risk of having a chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Furthermore, appropriate counselling about reproductive options can be provided to RB1 carriers and parents of children with Rb. As we have shown in previous studies, reproductive behaviour is influenced by Rb for many parents at increased risk for a child with Rb 8 9. Several patients with Rb in our cohort were unaware of the hereditary nature of their disease and conceived children who developed Rb and were not screened from birth, nor had the parents had the opportunity to consider other reproductive options, for example, prenatal diagnosis or preimplantation genetic diagnosis.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Furthermore, appropriate counselling about reproductive options can be provided to RB1 carriers and parents of children with Rb. As we have shown in previous studies, reproductive behaviour is influenced by Rb for many parents at increased risk for a child with Rb 8 9. Several patients with Rb in our cohort were unaware of the hereditary nature of their disease and conceived children who developed Rb and were not screened from birth, nor had the parents had the opportunity to consider other reproductive options, for example, prenatal diagnosis or preimplantation genetic diagnosis.…”
Section: Discussionmentioning
confidence: 78%
“…These eye exams would no longer be necessary if an increased risk could be excluded through DNA testing. Furthermore, knowledge of the presence of an RB1 mutation in the germline, or two RB1 mutations in the Rb tumour and none in the germline, can aid families in reproductive decision making,8 9 emphasising the clinical importance for RB1 mutation scanning.…”
Section: Introductionmentioning
confidence: 99%
“…Research has demonstrated that couples often experience the reproductive decision-making process as very difficult (Dekeuwer and Bateman 2013; Dommering et al 2010; Ormondroyd et al 2012). Feelings of uncertainty, regret, and guilt are common (Derks-Smeets et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…They usually also took a lead in the decision making process in that they were the ones who introduced and led the discussion. This however did not mean that it was their views or intentions that prevailed when the final decision was made as the other partner had the power to veto the decision [24][25][26] Among the study sample, only six women and one man were unemployed. All of other respondents were either in formal or informal employment.…”
Section: Discussionmentioning
confidence: 99%